Cushing's syndrome. (August 2017) - Daniel, Eleni; Newell-Price, John
Abstract: Endogenous Cushing's syndrome results from prolonged, excessive, inappropriate concentrations of circulating cortisol. Cushing's syndrome should be considered in patients with unusual features for age, patients with multiple and progressive features, children with decreasing height percentile and increasing weight, and patients with adrenal adenoma found incidentally. Endogenous Cushing's syndrome is more common in women than men. Adrenocorticotrophic hormone (ACTH)-dependent causes account for about 80% of cases. Of ACTH-dependent cases, 80% result from pituitary adenomas (Cushing's disease) and the remainder from ectopic ACTH secretion. Non-ACTH-dependent Cushing's syndrome is caused by benign adrenal adenomas in 60% and carcinomas in 40%. Specialist assessment and treatment warrants referral to major centres. For diagnosis, the most discriminating clinical features are thin skin, easy bruising and proximal myopathy. Biochemical diagnosis is by a combination of low-dose dexamethasone suppression tests, assessment of loss of circadian rhythm and urinary free cortisol. When differentiating pituitary and non-pituitary sources of ACTH, reliance should be placed on biochemical evaluation. Medical therapy is often used preoperatively to lower plasma cortisol, postoperatively to control concentrations in patients not cured, and after radiotherapy. Trans-sphenoidal surgery is the treatment of choice for Cushing's disease; laparoscopic bilateral adrenalectomy can be used in refractory cases.